2017
DOI: 10.1007/s13201-017-0624-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of natural and modified biomass of Sargassum sp. for removal of Cd2+ and Zn2+ from wastewater

Abstract: Natural as well as acid modified dead biomass of brown marine alga Sargassum sp. was employed for the elimination of cadmium and zinc ions from synthetic wastewater; batch mode experiments were carried out to optimize various factors like adsorbent dosage, contact time, pH, agitation speed and primary metal ions concentration at room temperature (298.15 K) for both types of adsorbents i.e. natural and acid treated. Application of Langmuir and Freundlich isotherms suggested that the modified biomass adsorbed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…For both sorbents, the maximum Cd(II) ion %R capability was obtained at the optimum agitation speed of 250 rpm. is result was in agreement with the study reported by Mahmood et al [58]. Generally, an increase in the speed of agitation speed resulted in outstanding pollutant uptake capabilities and the agitation helps in overcoming the resistance of external mass transfer.…”
Section: Effects Of Agitation Speedsupporting
confidence: 93%
“…For both sorbents, the maximum Cd(II) ion %R capability was obtained at the optimum agitation speed of 250 rpm. is result was in agreement with the study reported by Mahmood et al [58]. Generally, an increase in the speed of agitation speed resulted in outstanding pollutant uptake capabilities and the agitation helps in overcoming the resistance of external mass transfer.…”
Section: Effects Of Agitation Speedsupporting
confidence: 93%
“…Dead algal mass is reported to be more promising than living algae because it has a high metal ion sorption capacity at a high rate, and the adsorbed heavy metal ions present can easily be removed using de-ionized water or desorption agents [106]. There are several works on the use of many species of sargasso as biosorbents, and in the removal of pollutants, such as metal ions (e.g., Hg, Pb, Cu, Cd, Ni, Zn, Fe, and Cr), organic solvents, and organic dyes [107][108][109][110][111][112][113][114][115].…”
Section: Biosorption Potential Of Sargasso Biomassmentioning
confidence: 99%
“…Different processes are being used throughout the world for the removal of heavy and toxic metals from polluted water to make it drinkable. These processes include solvent extraction, membrane separation, micro & ultrafiltration, forward and reverse osmosis, coagulation, electrolysis, precipitation, phytoremediation, ion exchange and adsorption [22,23]. The adsorption of Co and Mn on low cost media such as alumina or bentonite seems to be an economically viable solution to make the polluted water of the Multan city areas as drinkable [24,25].…”
Section: Resultsmentioning
confidence: 99%